Advanced polyanionic electrode materials for potassium-ion batteries: Progresses, challenges and application prospects. (April 2022) - Zhang, Kai-Yang; Gu, Zhen-Yi; Ang, Edison Huixiang; Guo, Jin-Zhi; Wang, Xiao-Tong; Wang, Yinglin; Wu, Xing-Long
Graphical abstract: Advanced polyanionic electrode materials for potassium-ion batteries are meticulously introduced. The basic insights into the material design, electrochemical feature, and energy storage mechanism of polyanionic compound and supply their future optimization with reasonable perspectives and strategies. Abstract: Although potassium-ion batteries (KIBs) are considered a very promising energy storage system, their development for actual application still has a long way to go. Advanced electrode materials, as a fundamental component of KIBs, are essential for optimizing electrochemical performance and promoting effective energy storage. Due to their unique structural benefits in terms of cycle capability, strong ionic conductivity, and tunable operating voltage, polyanionic compounds are one type of viable electrode material for manufacturing high-performance KIBs. The huge size of K + ion, on the other hand, places great demands on polyanionic materials, which must be able to withstand severe structural deformation during K + intercalation/delamination. To maintain steady electrochemical performance, it is critical to follow the appropriate design guidelines for electrode materials. This paper provides a summary of current advancements in polyanionic compound for KIBs, with a focus on electrode material structural design. The effects of various parameters on electrochemical performance are examined and summarized. In addition, various viable solutions are proposed to address the impending issues posed by polyanionic compounds for KIBs, with the hope of providing a clearer picture of the field's future development path.